Influence of Traditional Chinese Medicines on Bioaccessibility and Speciation of Arsenic in Realgar and Mercury in Cinnabar - Yan, L.L.; Chen, J.J.; Zhou, Y.; Hu, J. (Asian Journal of Chemistry, 2015)
Influence of traditional Chinese medicines on the bioaccessibility and speciation of arsenic in realgar and mercury in cinnabar was observed using in vitro digestion dialysis method. Inductively coupled plasma-mass spectrometry (ICP-MS) and its hyphenation with high-performance liquid chromatography were used to determine the contents of arsenic, mercury and their species, respectively. Here, traditional Chinese medicines including Radix glycyrrhizae, Vigna radiata and Folium isatidis had a positive influence on arsenic bioaccessibility. Radix glycyrrhizae and Vigna radiata improved the content of As(III) and reduced As(V) in gastric phase, while both of them reduced the content of As(III) in intestinal phase. In addition, Radix glycyrrhizae, Vigna radiata and Rhizoma smilacis glabrae had significant effects on bioaccessibility of mercury in cinnabar. In cinnabar and cinnabar-traditional Chinese medicines mixtures, Hg2+ is the only specie. The results indicate that Hg2+ doesn't transform to CH3Hg+ of higher toxicity.